Le fratture di polso e la lesione di Galeazzi - Vicenti, G.; Abate, A.; Carrozzo, M.; Colella, A.; Moretti, B. (Lo Scalpello - Journal, 2018)
DISTAL RADIUS AND GALEAZZI FRACTURESFractures of the distal radius are the most common fractures in children and adolescents, accounting for 40% of allfractures. Distal radius fractures occur most frequently during early adolescence. The mechanism of injury is usually afall on a hyperextended wrist. Fractures of the distal radius usually involve the metaphysis. Although physeal (growthplate) injuries are relatively rare, they must be considered carefully because they can result in premature growtharrest. Shortening of the radius can lead to ulnar impaction and triangular fibrocartilage complex (TFCC) tears. Thetwo most common types of distal radial metaphyseal fractures are torus fractures and greenstick fractures. A completefracture passes through both cortices of the distal metaphysis (distal third) of the radius and/or ulna, often withdisplacement. A Galeazzi fracture is a fracture of the distal third of the radius along with dislocation of the distalradioulnar joint or ulnar physeal separation (Galeazzi-equivalent fracture). This article reviews current conceptsregarding distal forearm fractures in children and adolescents, with particular attention to classification,recommended treatment options and long term complications.